Budidaya Kappaphycus striatum dari Hasil Pembibitan Bersama Makroalga Coklat (Sargassum SP) dalam Keramba Jaring Apung di Pulau Semau Kabupaten Kupang - Safronius Avatorio Peol; Welem L. Turupadang; Yulianus Linggi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Kappaphycus striatum seaweed is a strategic commodity producing high-value carrageenan and is widely cultivated in Indonesia. This study aims to assess the growth rate of Kappaphycus striatum which is seeded with Sargassum sp. in floating net cages (KJA) and then cultivated using the longline method in the waters of Batuhopon, Huilelot Village, Semau Island, Kupang Regency. The study was conducted during August–October 2025 using a Completely Randomized Design (CRD) with four treatments, namely P0 (5 kg Kappaphycus striatum + 0 kg Sargassum sp.), P1 (4.5 kg Kappaphycus striatum + 0.5 kg Sargassum sp.), P2 (3.5 kg Kappaphycus striatum + 1.5 kg Sargassum sp.), and P3 (2.5 kg Kappaphycus striatum + 2.5 kg Sargassum sp.). Observed parameters included daily growth rate, specific growth rate, absolute growth rate, ice-ice disease incidence, and water quality. Data were analyzed using Analysis of Variance (ANOVA). The results showed that the average daily growth rate in all treatments increased until the fifth week, but some treatments decreased in the sixth week. Treatment P0 provided the highest and most stable growth. The results of the ANOVA test showed that the treatment had no significant effect on the daily growth rate (P>0.05), but had a significant effect on the specific growth rate and absolute growth (P<0.05). The highest absolute growth was obtained in treatment P0, followed by P1, P3, and P2. The incidence of ice-ice disease increased gradually from 5% in the first week to 35% in the sixth week. Water quality parameters during the study were in the range that still supported seaweed growth, namely temperature 28–30°C, salinity 30–33 ppt, pH 7.5–8.0, depth 20 cm, and current velocity 0.3–0.4 m/s.